2022
DOI: 10.3389/fpubh.2022.1072052
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective of correlation between maternal blood lead levels and risks of preeclampsia: An updated systematic review and meta-analysis

Abstract: BackgroundPreeclampsia (PE) is a specific hypertensive disorder in pregnancy. Lead (Pb) is a heavy metal that affects women's reproductive health. However, it is unclear whether lead exposure during can predispose maternal risk of developing preeclampsia. This systematic review and meta-analysis study aimed to explore the association.MethodsWe searched studies from three databases (PubMed, Web of Science, Embase). Only case-control, cross-sectional, and cohort studies reporting maternal blood lead levels (BLL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…However, we also noted some limitations in our study. The studies that met the inclusion criteria were still limited compared to other heavy metal studies (Zhong, et al 2022), this con ned us from exploring deeper. Furthermore, some studies reported the correlation between Cd and preeclampsia but did not report their data completely, and hence we could not pool them together for further analysis (Kovalchuk, et al 2013;Osorio-Yañez, et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, we also noted some limitations in our study. The studies that met the inclusion criteria were still limited compared to other heavy metal studies (Zhong, et al 2022), this con ned us from exploring deeper. Furthermore, some studies reported the correlation between Cd and preeclampsia but did not report their data completely, and hence we could not pool them together for further analysis (Kovalchuk, et al 2013;Osorio-Yañez, et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, we also noted some limitations in our study. The studies that met the inclusion criteria were still limited compared to other heavy metal studies (83), which confined us from exploring deeper. Furthermore, some studies reported the correlation between Cd and preeclampsia but did not report their data completely, and hence, we could not pool them together for further analysis (36,38).…”
Section: Discussionmentioning
confidence: 99%
“…There are no known safe levels of exposure to toxic metals [17] and exposure is associated with a number of adverse biological effects including inflammation and oxidative stress [18,19]. Exposure to toxic metals during pregnancy may be associated with the development of pregnancy complications (gestational diabetes, hypertensive disorders) as well as adverse birth outcomes including preterm birth and small for gestational age [20][21][22][23]. Moreover, these effects may persist well into later life, for both the gestational parent and child, potentially contributing to life-long risk of developing several chronic diseases (Type 2 Diabetes, hypertension).…”
Section: Introductionmentioning
confidence: 99%